Mesenchymal Stromal Cell Homing: Mechanisms and Strategies for Improvement - Ullah, Mujib; Liu, Daniel D.; Thakor, Avnesh S. (iScience, 2019)
Mesenchymal stromal cells (MSCs) have been widely investigated for their therapeutic potential in regenerative medicine, owing to their ability to home damaged tissue and serve as a reservoir of growth factors and regenerative molecules. As such, clinical applications of MSCs are reliant on these cells successfully migrating to the desired tissue following their administration. Unfortunately, MSC homing is inefficient, with only a small percentage of cells reaching the target tissue following systemic administration. This attrition represents a major bottleneck in realizing the full therapeutic potential of MSC-based therapies. Accordingly, a variety of strategies have been employed in the hope of improving this process. Here, we review the molecular mechanisms underlying MSC homing, based on a multistep model involving (1) initial tethering by selectins, (2) activation by cytokines, (3) arrest by integrins, (4) diapedesis or transmigration using matrix remodelers, and (5) extravascular migration toward chemokine gradients. We then review the various strategies that have been investigated for improving MSC homing, including genetic modification, cell surface engineering, in vitro priming of MSCs, and in particular, ultrasound techniques, which have recently gained significant interest. Contextualizing these strategies within the multistep homing model emphasizes that our ability to optimize this process hinges on our understanding of its molecular mechanisms. Moving forward, it is only with a combined effort of basic biology and translational work that the potential of MSC-based therapies can be realized. [Display omitted] •Mesenchymal stromal cells (MSCs) are a promising platform for regenerative medicine•A major bottleneck of MSC therapies is their efficiency in homing damaged tissue•MSC homing is a multi-step process involving specific molecular interactions•A variety of strategies have been employed to optimize MSC homing Biological Sciences; Cell Biology; Stem Cells Research